Policy Driven Institutional Transformation at FKIP Universitas Sriwijaya (1960–2024): The Confluence of Local Adaptation and National Education Reform in Indonesia - Syafruddin Yusuf; Muhammad Reza Pahlevi; Tomy Wijaya (Analisis Sejarah, 2025)
This research examines the institutional evolution of FKIP Universitas Sriwijaya (1960-2024) within the conflict between centralized national education policy and local reactions. This research improves the study of Indonesian higher education by explaining how government actions, political factors, and local efforts have shaped the development of FKIPs. Historical methodology was systematically employed through four stages: heuristics, source criticism, interpretation, and historiography. Primary sources included institutional archives, governmental decrees, and interviews with pivotal figures. The results indicate that FKIP’s structural modifications were not solely administrative but stemmed from a complex process of negotiation and contestation. This research enhances the comprehension of institutional dynamics in postcolonial higher education by emphasizing the interplay between central policies and local adaptations. FKIP Universitas Sriwijaya exemplifies the evolution of teacher education institutions in response to regulatory pressures while preserving their societal significance.